Avaliação da influência de diferentes inóculos do isolado humano (Portland -I) de Giardia duodenalis sobre a cinética da infecção e no desenvolvimento de alterações patológicas no intestino delgado de gerbils (Meriones unguiculatus) experimentalmente infectados - Araújo, Núbia da Silva (2006)
Giardia duodenalis is, today, considered serious problem of public health attacking individuals, independent of characteristics cultural or socioeconomic. To compare the kinetics of the infection and pathological alterations in the small intestine, produced by Giardia duodenalis, 72 gerbils, were divided in 6 groups (A to F), being A the control and the others inoculated with doses of 10, 102,103,104 and 105 trophozoites of isolated Portland-1. For the accompaniment of the kinetics of the infection coprologics exams were made, daily, until the 35th day after the inoculation. Once detected in the feces, the cysts were separate for flotation in sucrose gradient and counted in Newbauer chamber. For the accompaniment of the development of histopathological alterations, 3 animals of each group were sacrificed on the 5, 17, 23 and 35 days after the inoculation. Three portions of the upper small intestine were removed. These were processed for the count of the trophozoites number stuck to the mucous membrane, for the histopathology analysis in HE and for scanning electron microscopy. Was observed pre-patent period of 12 days, with intermittent elimination until the 35th day after inoculation. Differences statistically significant were observed, among the medium number of recovered trophozoites, for group, in the days of sacrifice and positive correlation between inoculum dose and the number of recovered trophozoites. Morfometry was observed fall in the value of the villon/depth ratio in all the groups, when compared to the group it controls, being observed atrophy of the villon and hyperplasy of the depths. The scanning electron microscopy demonstrated, an increase in the mucus production in the inoculated animals and presence of trophozoites niches in the top and base of the villons. This study demonstrated that, the dose of the trophozoites inoculum doesn't interfere in the capacity to happen infection, nor in the development of alterations histopathological generated by the colonization of the intestine by trophozoites.